Adipose Tissue Compartments, Inflammation, and Cardiovascular Risk in the Context of Depression - Stapel, Britta; Jelinic, Maria; Drummond, Grant R.; Hartung, Dagmar; Kahl, Kai G. (Frontiers in Psychiatry, 2022)
The neurobiological and behavioral underpinnings linking mental disorders, in particular, major depressive disorder (MDD), with cardiovascular disorders are a matter of debate. Recent research focuses on visceral (intra-abdominal and epicardial) adipose tissue and inflammation and their impact on the development of cardiometabolic disorders. Intra-abdominal adipose tissue is defined as an endocrine active fat compartment surrounding inner organs and is associated with type 2 diabetes mellitus, a risk factor for the later development of cardiovascular disorders. Epicardial (pericardial) adipose tissue is a fat compartment surrounding the heart with close proximity to the arteries supporting the heart. Visceral adipose tissue (VAT) is an important source of inflammatory mediators that, in concert with other risk factors, plays a leading role in cardiovascular diseases. In conjunction with the behavioral (physical inactivity, sedentary lifestyle), psychological (adherence problems), and hormonal (dysfunction of the hypothalamus–pituitary–adrenal axis with subsequent hypercortisolism) alterations frequently accompanying MDD, an enhanced risk for cardiovascular disorders results.